2015
DOI: 10.1016/j.jfda.2015.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidation, angiotensin converting enzyme inhibition activity, nattokinase, and antihypertension of Bacillus subtilis (natto)-fermented pigeon pea

Abstract: Because of the high incidence of cardiovascular diseases in Asian countries, traditional fermented foods from Asia have been increasingly investigated for antiatherosclerotic effects. This study investigated the production of nattokinase, a serine fibrinolytic enzyme, in pigeon pea by Bacillus subtilis fermentation. B. subtilis 14714, B. subtilis 14715, B. subtilis 14716, and B. subtilis 14718 were employed to produce nattokinase. The highest nattokinase activity in pigeon pea was obtained using B. subtilis 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 32 publications
2
53
0
1
Order By: Relevance
“…Small peptides are generally accepted as the main substance that induces potent ACE-inhibitory activity (Lee et al, 2015;Rui et al, 2015). Our results also correspond to the generation of small peptides caused by the strong proteolytic capacity of A. elegans DCY-1, leading to observation of significant ACE-inhibitory activity in the fermented soymilk residues.…”
Section: Effect Of Ssf On Ace-inhibitory Activity Of Soymilk Residuessupporting
confidence: 77%
See 1 more Smart Citation
“…Small peptides are generally accepted as the main substance that induces potent ACE-inhibitory activity (Lee et al, 2015;Rui et al, 2015). Our results also correspond to the generation of small peptides caused by the strong proteolytic capacity of A. elegans DCY-1, leading to observation of significant ACE-inhibitory activity in the fermented soymilk residues.…”
Section: Effect Of Ssf On Ace-inhibitory Activity Of Soymilk Residuessupporting
confidence: 77%
“…The highest inhibition ratio (61.17% ± 0.94%) was obtained at the end of the fermentation process, which was possibly caused by the accumulation of bioactive peptides in the soymilk residues. Studies reported (B.-H. Lee, Lai, & Wu, 2015;Torino et al, 2013) that fermented cereals showed higher ACE-inhibitory activity than non-fermented cereals, suggesting that A. elegans DCY-1 in the present study possibly produced ACE-inhibitory substances Values are presented as means ± SD (n = 3), and means in the same row with different lower case letters (a, b, c, d) are significantly different (p < 0.05). Figure 2.…”
Section: Effect Of Ssf On Ace-inhibitory Activity Of Soymilk Residuesmentioning
confidence: 55%
“…The European Society of Hypertension reco mm ends diet and lifestyle approaches as a basis for prevention and treatment of hypertension. From animal model, it was both water extracts of pigeon pea and water extracts of B. subtilis fermented pigeon pea improved systolic blood pressure and diastolic blood pressure in spontaneously hypertensive rats (Lee et al 2015).…”
Section: Health Benefitsmentioning
confidence: 96%
“…In addition, it has been studied that fermentation increases the phenolic contents of legume seeds (Oboh, Ademiluyi, & Akindahunsi, ). While the medicinal properties of fermented legume seeds including fermented pigeon pea, Bambara groundnut, African locust bean, and soybean in the management of CVD such as hypertension has been reported (Ademiluyi & Oboh, ; Lee, Lai, & Wu, ), the possible underlying mechanisms have not been sufficiently studied. Therefore, this study was designed to investigate the modulatory effect of extracts from fermented locust bean and soybean on activities of AChE, PDE‐5′, arginase, and ecto‐5′nucleosidase enzymes which are linked to endothelial function and CVD.…”
Section: Introductionmentioning
confidence: 99%